LIMITS OF INTERNATIONAL INVOLVEMENT N THE SOUTHERN CAUCASUS: HE OSCE MEDIATION IN THE NAGORNO-KARABAKH CONFLICT (1992-1996) - GEUKJIAN, Ohannes (CENTRAL ASIA AND THE CAUCASUS, 2006)
The aim of this article is to examine and analyze the mediation of the Organization for Security and Cooperation in Europe (OSCE) in the Nagorno-Karabakh (N-K) conflict from 1992 to 1996, and the internal and external difficulties that hampered its peacemaking efforts. Also, the aim is to analyze the positions of the external (Russia) and internal (Armenia, Azerbaijan, Karabakh leadership) actors with respect to the peace plans presented by the OSCE and highlight the causes that con-tributed to their failure. In this context, much emphasis is put on the peace strategy implemented by the OSCE for conflict resolution in N-K, and the position of Russia which tried to sideline the OSCE to keep the Southern Caucasus under its direct political and economic influence. This article also stresses the role of Russia as a major regional actor in the N-K conflict and the prospects for possible cooperation between Russia and the OSCE from 1992 to 1996. The founding Helsinki Act in August 1975 that formally established the Conference for Security and Cooperation in Europe (CSCE), OSCE since 1994, has been viewed as an organization without a strong mandate to promote the peaceful resolution of ethnic conflicts and other disputes between and within member states.1 A key development in the mediation to resolve the N-K conflict was the United Nation’s agreement in late 1992 to let the OSCE become the main leading international body in the management and resolution of the N-K conflict.2 The OSCE became officially involved in the N-K conflict on 24 March, 1992, when its Ministerial Council adopted a decision to convene in Minsk (Belarus) under the auspices of the OSCE to provide an ongoing forum for the negotiation of a peaceful settlement of the N-K conflict between Armenia and Azerbaijan3 (two former Soviet republics which declared independence after the demise of the Soviet Union in 1991). In this way the idea of a “Minsk Conference” was born. In this context, Armenia, Azerbaijan, and ten other OSCE members (the Czech Republic, Slovakia, Germany, Sweden, Belarus, France, Italy, the Russian Federation, the U.S. and Turkey) agreed to take part in the “Minsk Conference.” Also, representatives of Karabakh Armenians and Azerbaijanis would participate. The “Minsk Conference” did not convene because of the escalation of the fighting in 1992 in N-K between the Armenians and Azerbaijanis. Hence, the “Minsk Conference "became instead the Minsk Group with the Italian deputy Foreign Minister as its first Chairman.4 At this period the aims of the OSCE were first to arrange a ceasefire in N-K and then commence negotiations between the parties to the conflict. The OSCE Stockholm meeting on 14 December 1992 that was on the verge of implementing a full ceasefire agreement in N-K failed because of Azerbaijan’s refusal.5